Deep-sea anemones (Cnidaria, Actiniaria) from off the northeastern coast of Brazil: new records and description of Stephanauge prima sp. nov. - Targino, Alessandra K. G.; Melo, Yago A. De; Gomes, Paula B. (Zootaxa, 2025)
Deep-sea anemones (order Actiniaria) are a diverse group of cnidarians found in basically all marine habitats, from soft sediments to hydrothermal vents and cold seeps. From the waters of Brazil, in the Southern Atlantic Ocean, the deep actinian fauna has been described to encompass 14 sea anemones species, belonging to three families: Hormathiidae, Amphianthidae and Actinoscyphiidae. Here we analyze material trawled from the Potiguar Basin, off the northeast coast of Brazil. We provide new occurrence records for Chondrophellia coronata (Verrill, 1883), Actinoscyphia saginata (Verrill, 1882), Amphianthus bathybium Hertwig, 1882, and Amphianthus michaelsarsi Carlgren, 1934. We also describe a new Amphianthidae species, Stephanauge prima sp. nov. This increases the total number of deep actinians found in Brazil to 17 and provides context for discussing the representativeness of these families and the potential richness of Actiniaria in deep Brazilian waters.